Future fish emissions: Insights from modeling foresight scenarios of regional fish supply and demand - Chan, Chin Yee; Tran, Nhuong; Schindler, Lisa (WorldFish, 2024)
A post-model analysis was used to estimate the future GHG emissions associated with aquatic foods across the different regions and subregions under this study. In direct comparison to terrestrial meats, capture fisheries and aquaculture production exhibit relatively low GHG emissions, signifying their distinct role in reducing food system emissions while sustainably fighting malnourishment. Nevertheless, growing production under the High scenario in South Asia is projected to result in substantial GHG emissions in the region by 2050. Our results depict aquaculture as the dominant source of emissions by 2035, as those from capture fisheries are expected to plateau. Technological progress and green investments show potential for the sustainable intensification of aquaculture by reducing emissions, increasing output, and adapting to climate impacts. Notable low-emission interventions include implementing co-cultures in aquaponics and optimizing feed and feeding methods, as well as incorporating seaweed farming into aquaculture. Combined rice and fish production in regions with high rates of rice consumption and nutrient deficiencies could benefit human and planetary health by reducing emissions and increasing food production.